Insight into the Role of Dental Pulp Stem Cells in Regenerative Therapy - Shinichiro Yoshida; Atsushi Tomokiyo; Daigaku Hasegawa; Sayuri Hamano; Hideki Sugii; Hidefumi Maeda (Biology, 2020)
Mesenchymal stem cells (MSCs) have the capacity for self-renewal and multilineage differentiation potential, and are considered a promising cell population for cell-based therapy and tissue regeneration. MSCs are isolated from various organs including dental pulp, which originates from cranial neural crest-derived ectomesenchyme. Recently, dental pulp stem cells (DPSCs) and stem cells from human exfoliated deciduous teeth (SHEDs) have been isolated from dental pulp tissue of adult permanent teeth and deciduous teeth, respectively. Because of their MSC-like characteristics such as high growth capacity, multipotency, expression of MSC-related markers, and immunomodulatory effects, they are suggested to be an important cell source for tissue regeneration. Here, we review the features of these cells, their potential to regenerate damaged tissues, and the recently acquired understanding of their potential for clinical application in regenerative medicine.